SOCIAL CONFLICT AND JUDICIAL PRACTICE IN LITHUANIA - Bakševičienė, Rūta (Teisė, 2015)
Law, as a social phenomenon reflects and includes in it’s content (identifies) the peculiarities of social phenomena, it’s content and emerging problems. Hence, system judicial problematic issues should not be left only for their analysis only to sociologists and politicians, as if law could function isolated from the conditions of social peculiarities. It is the aim of this article to show the link among problematic issues in law (the increasing number of law suits, mistrust of courts) and social peculiarities (certain developed judicial social traditions, the adaptivity of social circles aiming to retain and occupy certain positions). The object of the research of this article is the relation between social conflict and judicial practice in Lithuania, i.e. how one factor may be the reason and the consequence of the other. Both, judicial and social conflicts in the article are used in their broadest sense (conflict as a relation among state institutions, the relation of mistrust, judicial practice as a law making, court practice etc.).The peak of quarrel (conflict) both in a social and judicial sense apparently is reached when subjects apply to the court. Modern law, which is characterized by the amount of procedural forms, reflects this “critical” moment of the quarrel and further development of it in the shape of the magnitude of judicial norms. In fact, the advancement of the state is often judged by the development and quantity of procedural forms. In this sense nobody could call Lithuanian law and judicial system as retarded. All in all there are 63 courts in Lithuania. This figure reaches 63, (Constitutional court of Lithuania including) for the population of 2 943 472 inhabitants. The number of population decreased by 12,6 percent (440,6 thousands) during the decade (from 2001 years till the beginning of the year 2012). But the court system did not diminish. The law suits increased. Courts increasingly complain of ever increasing number of law suits and the amount of work. So, the situation is that a person commands a variety of means to defend his rights in a sense of procedural/institutional forms. On the other hand, it’s the situation when nobody is satisfied, and it seems there is no end in making the system of dispute resolution more perfect, and the entire dissatisfaction with the system (including the criticism of courts) is increasingly addressed to courts or prietrial institutions. From the sociological point of view the before mentioned situation may be compared to the fashion of conflicts which precludes animosity to any social group, phenomenon, situation. In a sense it has become a tradition. Thus the improvement of procedural forms in law, organizational judicial means, do not solve the problem. On the other hand, in as social sense a certain animosity among positions as maintenance of traditions or balance may become in a certain sense useful for the justification of the existence of any side in the conflict: one side criticizes the other works, undergoes the criticism of society, which encourages another criticism. When analyzing the above mentioned situation of position convenience, interesting situation emerges regarding real judicial and court practice. It’s not likely judging from these quarters that the number of law suits is diminishing. On the contrary, what concerns peace treaties in courts, mediation and other court practice signifies something else. Thus, it seems that the situation has developed when one part can comfortably criticize and the other can adjustingly react to criticism, thus making a “balance” and “tradition” jointly maintaining permanent traits, necessary for adjustment. Such social beliefs and traditions hardly change, although whole generations pay for it with the quality of life. The forecast could be that the situation will change naturally, i.e. the rate of it’s increase may be such, that it becomes unbearable even to those, to whom it is comfortable at present. There are such signs. They can be observed in the implementation of organizational means, in the change of court laws with the aim of reducing the number of law suits, in making the process more quick and simple. External factors may change the situation, e.g. the control of institutions by the European Union. Certain personalities may change it on condition that they are independent from state institutions occupying adjustive “positions”. The input of law scientists in this sense could be a fine example of cooperation of state and society.